164k views
0 votes
Divide using long division. Check your answer.

(5x2 - 2x + 1) = (x - 1)
The quotient is
with remainder

User Kirti Zare
by
5.3k points

1 Answer

2 votes

Answer:

x = 4

Explanation:

(5x2 - 2x + 1) = (x - 1)

Simplify by multiplying 5 and 2.

(10 - 2x + 1) = (x - 1)

Combine like terms. Remove parentheses.

11 - 2x = x - 1

Cancel out - 2x to get the variable on one side.

- 2x + 2x = 0 x + 2x = 3x

11 = 3x - 1

Do the same with the 1.

12 = 3x

Divide.

x = 4

User Exsnake
by
5.5k points